E-Commerce: Advantages and Challenges (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
This research includes electronic trade subject that is used in the world these days for most trade deals, thus it leads to quick development in international trade business for earning money and time. The massive development in earnings has led to great competition; while the world has benefited from this type of trade while it still under development daily. On the contrary, the third world nations did not enter this field of trade only from a narrow way in spite of its benefits and challenges. In this research, we have stopped on the benefits and risks to put electronic trade on balance and encourage entering and using this field for servicing nations and individuals.